Stress induced phosphoprotein 1 overexpression controls proliferation, migration and invasion and is associated with poor survival in oral squamous cell carcinoma - Dourado, Mauricio Rocha; Elseragy, Amr; da Costa, Bruno Cesar; Téo, Fábio Haach; Guimarães, Gustavo Narvaes; Machado, Renato Assis; Risteli, Maija; Wahbi, Wafa; Gurgel Rocha, Clarissa Araujo; Paranaíba, Lívia Máris Ribeiro; González-Arriagada, Wilfredo Alejandro; da Silva, Sabrina Daniela; et al. (Frontiers in Oncology, 2023)
Objective: Although there have been remarkable achievements in the molecular landscape of oral squamous cell carcinoma (OSCC) in recent years, bringing advances in the understanding of its pathogenesis, development and progression, little has been applied in the prognosis and choosing the optimal treatment. In this study, we explored the influence of the stress induced phosphoprotein 1 (STIP1), which is frequently reported to be highly expressed in many cancers, in OSCCs. Methods: STIP1 expression was assessed in the TCGA database and in two independent cohorts by immunohistochemistry. Knockdown strategy was applied in OSCC cell lines to determine the impact of STIP1 on viability, proliferation, migration and invasion. The zebrafish model was applied for studying tumor formation and metastasis in vivo. The association of STIP1 and miR-218-5p was explored by bioinformatics and mimics transfection. Results: STIP1 was highly expressed in OSCCs and significantly associated with shortened survival and higher risk of recurrence. STIP1 down-regulation decreased proliferation, migration and invasion of tumor cells, and reduced the number of metastases in the Zebrafish model. STIP1 and miR-218-5p were inversely expressed, and the transfection of miR-218-5p mimics into OSCC cells decreased STIP1 levels as well as proliferation, migration and invasion. Conclusion: Our findings show that STIP1 overexpression, which is inversely associated with miR-218-5p levels, contributes to OSCC aggressiveness by controlling proliferation, migration and invasion and is a determinant of poor prognosis.